Analisis Efektivitas Sistem Perekrutan dan Seleksi Karyawan di PT. PLN (Persero) UP3 Nias Gunungsitoli (Jurnal Riset Manajemen dan Akuntansi, 2025)
Human resources (HR) are a crucial element in achieving an organization's vision and mission, particularly through an effective employee recruitment and selection process. This study examines the effectiveness of the recruitment and selection system at PT. PLN (Persero) UP3 Nias Gunungsitoli, which is responsible for providing reliable and quality electricity services to the Nias community. The recruitment and selection process not only emphasizes the technical competence of candidates but also the alignment of their values, culture, and vision with that of the company, which influences employee loyalty, contribution, and teamwork. The study discusses various definitions of effectiveness as well as the fundamental concepts of recruitment and selection systems based on existing literature, serving as the basis for evaluating the implementation of the system in the field. The objectives of this study are to assess the recruitment and selection system implemented at PT. PLN (Persero) UP3 Nias Gunungsitoli and to identify the factors that hinder its effectiveness. A qualitative research approach was employed, utilizing data collection techniques such as observation, interviews, and documentation review. The findings indicate that the recruitment and selection system at PT. PLN (Persero) UP3 Nias Gunungsitoli utilizes digital technology to assess both technical competencies and soft skills. Although a transparent process has been implemented, challenges remain due to digital infrastructure limitations and varying levels of candidate readiness in using technology. The study recommends solutions such as enhanced access and preliminary training for applicants to ensure a smooth and secure selection process.